Nasopharyngeal Carcinoma Profile in dr. Cipto Mangunkusumo Hospital Year 2013 - Soehartati Argadikoesoema Gondhowiardjo; Lidya Meidania; Fajar Senoaji; Sri Mutya Sekarutami (Radioterapi & Onkologi Indonesia, 2019)
Background: Nasopharyngeal carcinoma (NPC) remains as a health burden in Indonesia. It is one of most common cancers in Indonesia, with an overall incidence estimated at 6.2/100,000 or 12,000 new cases per year. Unfortunately, many of these cases are unregistered due to several factors, such as lack of national cancer registry. In most developing countries, cancer registration often begins in hospitals. Hospital-Based Cancer Registry (HBCR) provides the initial and major source of information on patients that leads to the set-up of a population-based registry.Materials and Methods: This was a descriptive retrospective study of all registered NPC patient in HBCR, from January-December 2013. All registered NPC patients in HBCR in the year 2013 is included.Results: There were 299 NPC patients, with a male-to-female ratio of 2.4:1. Median age was 47 years old, with majority of age between 40-49 years old (27.4%). Most common type of histology was undifferentiated NPC (85%). Most patients presented with locally advanced disease, with majority of stage IVA (33.9%). Chemoradiation remained as standard treatment for locally advanced NPC (84.1%).Conclusion: Demographic data of patients, such as age and sex, are consistent with previous studies. Whereas racial distribution was not parallel with previous studies, maybe due to its lack of available data. Moreover, most common histopathology type and presentation was undifferentiated NPC and patients with Stage III to IV cancer.